2018
DOI: 10.3389/fphar.2018.00237
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NMDA Receptors Prevents the Loss of BDNF Function Induced by Amyloid β

Abstract: Brain-derived neurotrophic factor (BDNF) plays important functions in cell survival and differentiation, neuronal outgrowth and plasticity. In Alzheimer’s disease (AD), BDNF signaling is known to be impaired, partially because amyloid β (Aβ) induces truncation of BDNF main receptor, TrkB-full length (TrkB-FL). We have previously shown that such truncation is mediated by calpains, results in the formation of an intracellular domain (ICD) fragment and causes BDNF loss of function. Since calpains are Ca2+-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 108 publications
4
33
0
Order By: Relevance
“…In accordance with previous studies ( Tanqueiro et al., 2018 ), cultured cortical neurons exposed to Aβ 25–35 for 24 h, showed a significant decrease in the number of dendritic protrusions when compared to the control condition (Aβ: 6.58 ± 0.153 vs. control: 8.07 ± 0.153; p < 0.05, two-way ANOVA with Tukey’s multiple comparisons test; n = 5) ( Figure 8C ). Remarkably, the Aβ-induced impairment in the number of dendritic protrusions was absent when neurons were co-treated with 50 nM KTP-NH 2 (Aβ + KTP-NH 2 : 9.60 ± 0.134 vs. control: 8.07 ± 0.153; p < 0.05, two-way ANOVA with Tukey’s multiple comparisons test; n = 5).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies ( Tanqueiro et al., 2018 ), cultured cortical neurons exposed to Aβ 25–35 for 24 h, showed a significant decrease in the number of dendritic protrusions when compared to the control condition (Aβ: 6.58 ± 0.153 vs. control: 8.07 ± 0.153; p < 0.05, two-way ANOVA with Tukey’s multiple comparisons test; n = 5) ( Figure 8C ). Remarkably, the Aβ-induced impairment in the number of dendritic protrusions was absent when neurons were co-treated with 50 nM KTP-NH 2 (Aβ + KTP-NH 2 : 9.60 ± 0.134 vs. control: 8.07 ± 0.153; p < 0.05, two-way ANOVA with Tukey’s multiple comparisons test; n = 5).…”
Section: Resultssupporting
confidence: 92%
“…In order to evaluate the neuroprotective effect of drug treatment, spine density was counted as previously done in our lab (Tanqueiro et al, 2018). Briefly, primary neuronal cultures at DIV14 were fixed in 4% PFA in PBS (pH 7.4) for 15 min at RT, after being washed with PBS twice.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…In contrast, neurodegenerative conditions are known to increase activation of NMDA receptors and calciumpermeable AMPA receptors, leading to hippocampal synaptic plasticity impairment (Diógenes et al, 2012;Ferreira et al, 2017;Tanqueiro et al, 2018). There is plenty of evidence that under pathological conditions, A 2A receptor signalling is exacerbated, which contributes to pathogenesis and leads to early cognitive and synaptic dysfunction as well as neurodegeneration (Canas et al, 2009;Cognato et al, 2010;Batalha et al, 2013;Kadowaki-Horita et al, 2013;Kaster et al, 2015;Li et al, 2015a,b;Hu et al, 2016;Laurent et al, 2016;Viana da Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The overactivation of calpains in AD is associated with functional changes in several proteins involved in neuronal transmission, such as BDNF. Previous reports have shown that Aβ impairs BDNF function in a calpain-dependent manner (Jerónimo-Santos et al, 2015), whereas inhibition of eNMDAR can prevent Aβ-triggered impairment of BDNF action in long-term synaptic potentiation (Tanqueiro et al, 2018).…”
Section: The Old Man and The Alzheimer's Diseasementioning
confidence: 96%